Phantom blade model - advanced methodology for actuator disk modeling - Dos Reis Marioni, T.; Legras, G.; Link, S.; Embacher, M. (My University, 2019)
A good prediction of the unsteady behavior of the aerodynamic interactions between rotating and fixed parts is of great importance in the design of a helicopter, in particular for rear parts conception. In the present work, an unsteady actuator disk-like approach named Phantom Blade Model (PBM) is presented and results obtained are confronted to other numerical approaches and test data. This method allows (1) improved modeling of the rotor downwash and of the aerodynamic interactions compared to the classic, steady, actuator disk and (2) reduced pre-processing and computational times compared to high-fidelity CFD models with meshed blades. First, two academic cases for which experimental data is available, namely an isolated two-bladed rotor in hover and a ROBIN fuselage equipped with a four-bladed rotor in level flight, are used as validation cases for the PBM. Good agreement is observed with both tests and meshed-blades simulations, with reduced simulation time - 48% and 63% less CPU hours, respectively. Then, the PBM is applied to the Bluecopter® in forward flight, in which PBM is used for both main rotor and Fenestron®. Comparison between high-fidelity CFD/CSM simulations of a full helicopter, flight tests and unsteady actuator disk applied to a flying aircraft as presented here is new. Results with PBM of unsteady loads and pressure at the horizontal stabilizer are considerably close to the complete helicopter CFD/CSM simulations. Both numerical methods fairly capture the amplitudes, but slightly overestimate the average pressure compared to test data.